2021
DOI: 10.1007/s10661-021-09601-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal pollution and ecological risk in river water and sediments in a historically metal mined watershed, Northeast Japan

Abstract: the outlet of the tributary within each sub-watershed was also sampled to capture the diffusional pollution status. The distributions of Zn, Cu, Cd, Pb and As in river water and sediments, as well as their pollution characteristics and ecological risks, were analysed under different hydrological conditions. Our findings provide evidence of the ecological risk in surface water induced by Zn, Cu and Pb pollution in the Kosaka River system. In a high proportion of the sub-watershed, there was moderate to strong e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Practical experience shows that the Mahananda River is likely to be threatened by pollution, with seven sampling stations exceeding the hazard limit (HI ≤ 1) in the premonsoon season and two sampling stations exceeding the limit in the post-monsoon season. Ustao glu and coworkers investigated the status and contamination levels of 13 elements polluting seven rivers in the northeastern Giresun Basin in Turkey and showed that the levels of Al in the rivers exceeded the World Health Organization's acceptable limits and that the risk of cancer in both children and adults was lower in one river basin but higher in the remainder as a result of contamination with As, and other related studies have shown similar results [18,[26][27][28][29]. Numerous studies have shown that anthropogenic activities have led to elevated concentrations of the metal elements Cr and As in soils, waters, sediments, etc., with certain potential hazards to the ecological environment and human health.…”
Section: Introductionmentioning
confidence: 75%
“…Practical experience shows that the Mahananda River is likely to be threatened by pollution, with seven sampling stations exceeding the hazard limit (HI ≤ 1) in the premonsoon season and two sampling stations exceeding the limit in the post-monsoon season. Ustao glu and coworkers investigated the status and contamination levels of 13 elements polluting seven rivers in the northeastern Giresun Basin in Turkey and showed that the levels of Al in the rivers exceeded the World Health Organization's acceptable limits and that the risk of cancer in both children and adults was lower in one river basin but higher in the remainder as a result of contamination with As, and other related studies have shown similar results [18,[26][27][28][29]. Numerous studies have shown that anthropogenic activities have led to elevated concentrations of the metal elements Cr and As in soils, waters, sediments, etc., with certain potential hazards to the ecological environment and human health.…”
Section: Introductionmentioning
confidence: 75%
“…Soils of many mining communities have a lot of metal contaminants because of metal ores mining and milling [ 15 , 16 ]. Heavy metal (lead, mercury, arsenic, cadmium, chromium, zinc and nickel) pollution exists in the soil surrounding mines, posing persistent risks to public health [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on water ecological risk at home and abroad has focused on three main areas: firstly, theoretical research, such as defining the concept of water ecological risk, exploring the development of water ecological risk, constructing evaluation index systems and designing water ecological risk evaluation models [7][8][9][10]. The second is empirical research, using the evaluation index system and evaluation model to evaluate and analyse the research object [11][12][13][14][15]. The third is object research, mainly focusing on watersheds [11][12], plateaus [13], cities [14], and mining areas [15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The second is empirical research, using the evaluation index system and evaluation model to evaluate and analyse the research object [11][12][13][14][15]. The third is object research, mainly focusing on watersheds [11][12], plateaus [13], cities [14], and mining areas [15][16]. This paper takes mining areas as the primary research subject and combines them with watersheds and soils.…”
Section: Introductionmentioning
confidence: 99%